Global Gene Expression in Cyanobacterial Electron Transfer Mutants - Short, Kraig; Weir IV, George L. (My University, 2009)
In photosynthesis, microalgae such as cyanobacteria capture enormous amounts of solar energy and convert carbon dioxide (CO2) into biopolymers that support life on earth and hold great potential for production of carbon-neutral biofuels. The photosynthetic process involves electron transfer reactions mediated by reaction center and cytochrome bf protein complexes. The bf complex also functions in regulation of photosynthesis by mechanisms that are not fully understood. We used the marine cyanobacterium Synechococcus PCC 7002 and mutants with genetically altered cytochrome bf complexes to investigate the role of this complex in regulation of adaptive gene expression responses. Native and mutant Synechococcus cultures were grown in CO2-limited photosynthetic conditions, RNA molecules were extracted, and fluorescently labeled copies of these were hybridized to whole-genome microarrays ("gene chips") to detect gene expression levels. Numerous genes were differentially expressed in the cytochrome bf mutants, illustrating the importance of the bf complex for gene regulation and adaptation. The research contributes to understanding the regulation of electron transport in globally important microalgae and to potential biofuels applications of these organisms.
Keywords: Electron transfer; Mutants; Cyanobacteria; Biofuel; Synechococcus; Gene expression